Low-temperature solution-processed flexible NH3 gas sensors based on porous CuBr films derived from 2D Cu nanosheets - Juyoung Jin; Hyojin Bang; Seungyeon Kim; Yang, Hee Yun; Bae, Sukang; Seung Min Yu; Yonghun Kim; Jung-Dae Kwon; Hong Seung Kim; Tae-Wook Kim; Jongwon Yoon (Elsevier BV, 2025)
The sensitive and selective detection of ammonia (NH3) gas at sub-ppm level and room temperature has attracted significant attention due to its promising applications in environment monitoring and medical diagnosis. Furthermore, these applications require flexible and wearable functionalities for both potential and practical use. Here, we report an NH3 gas sensor based on a porous copper bromide (CuBr) film, converted from the two-dimensional (2D) copper nanosheets (Cu NSs). The porous CuBr film as a sensing material is prepared by an all-solution and vacuum-free process at low temperature, enabling device fabrication on a plastic substrate. The optimized gas sensor, achieved by controlling the morphology and surface coverage of the porous CuBr film, exhibits a sensitive and selective NH3 gas response at sub-ppm levels and room temperature. The mechanical bending test over 1000 bending cycles at a bending radius (r) of 2？mm reveals the feasibility of flexible and wearable applications.